All Welcome Here? Studies on Anti-Immigration Attitudes and Discriminatory Behaviour towards Ethnic Minorities in Irish and European Contexts - GUSCIUTE, EGLE (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2020)
The main aim of this thesis is to examine prejudice, via anti-immigration sentiment, and discriminatory behaviour in Ireland and other European countries. The thesis consists of four separate papers which constitute four empirical chapters. Studies 1, 2 and 3 use European Social Survey in addition to other datasets to examine attitudes towards different sub-groups of migrants. Study 4 examines discrimination via a field experiment. The thesis has three, broad, main aims: i) to examine the hypothesis that anti-migrant sentiment can be explained via the perceived objective and economic threat which migrants pose to the native population, ii) to examine attitudes towards specific sub-groups of migrants which reflect the current migratory inflows and public debate, with a particular focus on Muslim migrants and asylum seekers, and iii) to investigate the extent of discrimination towards ethnic minorities in the Irish context. Study 1 examines if individuals in occupations and sectors which i) are exposed to economic decline as measured by job losses, and ii) which have a greater share of migrants, are more likely to express anti-immigrant sentiment in the Irish context. The study finds that, consistent with the threat hypothesis, job losses and a greater share of migrants within occupational and sectoral levels are negatively associated with attitudes towards immigration and acceptance of migrants. Furthermore, the study finds that the change in job growth year-on-year has an impact on attitudes. Therefore suggesting that, in the short-term, job losses do lead to a decreased acceptance towards migrants for individuals affected by the economic decline. Study 2 considers the role of the threat hypothesis as a determinant of anti-asylum sentiment, cross-nationally. It considers i) if threat related to economic resources and the size of the ethnic group is associated with more negative sentiment and ii) if asylum seekers are perceived as a distinct sub-group of migrants in need of help and thus is there greater willingness to help and tolerance towards this group. The study finds that greater levels of generalised trust and trust in national institutions are associated with greater support towards asylum seekers. However, in contrast to the threat hypothesis, unemployed individuals and countries with higher rates of unemployment show greater support for asylum seekers rather than more resistance. Study 3 focusses on attitudes towards Muslim migrants. It examines i) if there is greater opposition towards Muslim migrants than towards migrants in general, and ii) if the threat hypothesis in relation to security, the size of ethnic group and integration account for anti-Muslim sentiment. The analysis shows that in most European countries there is significantly greater opposition to Muslim immigration than immigration in general, particularly in Eastern Europe. On the country level, objective measures of threat do not explain the pattern of cross-country variation. Countries with a higher share of Muslims and higher incidence of terrorist attacks are more welcoming towards further Muslim immigration. Furthermore, the study finds that women are more opposed to Muslim immigration than men. Study 4 collects primary data via a field experiment i) to detect discrimination in the Irish housing market and, ii) to measure the extent of this discrimination. The study uses established methods in the area of correspondence studies and focuses on Irish, Polish and Nigerian nationals. This field experiment is the first experiment on the housing rental market in the Irish context. The study finds evidence of ethnic and gender discrimination as ethnic minority applicants and men are less likely to be invited to view an apartment than Irish applicants and women. Findings suggest that Nigerian applicants are the most disadvantaged when looking for rental property.
APPROVED
Keywords: asylum-seekers; anti-Muslim attitudes; refugees; quantitative research; field experiment; threat; migrants; East versus West; rental housing market; Ireland; anti-immigration attitudes; Europe; prejudice; discrimination; economic threat; European Social Survey; immigration; integration